Analysis of discriminatory characteristics of a video sensor with an exponential correlation function - Gerasimov, V P; Kovalev, V D; Yu Darzhaniya, A; Magomedov, R A; Sokolova, E V; Klimenko, O V (IOP conference series. Materials Science and Engineering, 2020)
This article presents an analysis of the characteristics of the video sensors functioning both in the visible and "thermal" regions of the spectrum. The influence of errors caused by the non-linearity of the discriminatory characteristic (DC) in the idealized model is studied. The article is devoted to the refinement of the model, taking into account the constant exponent parameter and introducing its value into the algorithm implemented by the onboard video sensor.